2022
DOI: 10.1186/s12937-022-00770-4
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods study to determine the impact of COVID-19 on food security, food access and supply in regional Australia for consumers and food supply stakeholders

Abstract: Background The COVID-19 pandemic has impacted the Australian food supply through changed consumer purchasing patterns, and potentially, household food security. The aim of this study was to determine the impact of COVID-19 on the prevalence of food insecurity and food supply issues, and perspectives of food supply stakeholders in regional Australia. Methods A mixed-methods consumer survey and in-depth interviews with food supply stakeholders were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…Some hospitality businesses were forced to close due to social distancing restrictions; others adapted their business model to offer takeaway or home delivery [36]. The way in which consumers shopped in supermarkets also changed as individuals were encouraged to reduce the number of shopping trips taken to avoid the risk of infection, have only one member of the household shopping for food and alter the timing of the trip to avoid peak times [37]. There was also a significant increase in food deliveries and 'click and collect' shopping [37].…”
Section: Food System Disruptions At the Beginning Of The Covid-19 Pan...mentioning
confidence: 99%
“…Some hospitality businesses were forced to close due to social distancing restrictions; others adapted their business model to offer takeaway or home delivery [36]. The way in which consumers shopped in supermarkets also changed as individuals were encouraged to reduce the number of shopping trips taken to avoid the risk of infection, have only one member of the household shopping for food and alter the timing of the trip to avoid peak times [37]. There was also a significant increase in food deliveries and 'click and collect' shopping [37].…”
Section: Food System Disruptions At the Beginning Of The Covid-19 Pan...mentioning
confidence: 99%
“…The “just-in-time fulfillment” of food stocks presented issues when supply chains were inflexible and unable to respond to unprecedented demand. Thus, supply chain vulnerabilities were highlighted and resulted in empty supermarket shelves [ 8 , 9 ]. Businesses sought alternative suppliers, food prices increased, many hospitality businesses closed, the media spread misinformation, and consumers sought alternative food suppliers to meet their needs [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Region-based or local food purchasing is a potential solution to food supply issues, particularly during crises such as the COVID-19 pandemic. Recent evidence suggested that consumer demand resulted in surges in local food sales at farm gates or farmers’ markets [ 9 , 13 ]. In regional WA, some consumers preferred to shop at smaller outlets and roadside stalls instead of the large supermarkets [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders with interests in food security (e.g., policymakers, educators and extension specialists, members of civil society groups, and those within the food industry) play an important role in shaping access to healthy and sustainable diets [10]. Hence, stakeholders' views on what constitutes healthy practices and the role of traditional foods in promoting food security are important, as they will shape food availability and hence consumers' food choices in the supply chain [10]. Stakeholders' perspectives are important as one of the approaches applied to the development of community empowerment where stakeholders have different roles and responsibilities [11].…”
Section: Introductionmentioning
confidence: 99%